2020
DOI: 10.1177/2048872619848883
|View full text |Cite
|
Sign up to set email alerts
|

Serum potassium level on hospital arrival and survival after out-of-hospital cardiac arrest: The CRITICAL study in Osaka, Japan

Abstract: Background: Little is known about the association between serum potassium level on hospital arrival and neurological outcome after out-of-hospital cardiac arrest (OHCA). We investigated whether the serum potassium level on hospital arrival had prognostic indications for patients with OHCA. Methods: This prospective, multicenter observational study conducted in Osaka, Japan (CRITICAL study) enrolled consecutive patients with OHCA transported to 14 participating institutions from 2012 to 2016. We included adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…Ammonia and lactate levels were higher and pH levels were lower in the poor outcome group [28]. Shida et al [35] reported that high serum potassium level was significantly and dosedependently associated with poor neurological outcomes. The highest proportion of favorable neurological outcome was 44.8% in Q1 group (K ≤3.8 mEq/L), and the proportion of favorable neurological outcomes decreased as the serum potassium level increased.…”
Section: Metabolic Managementmentioning
confidence: 99%
“…Ammonia and lactate levels were higher and pH levels were lower in the poor outcome group [28]. Shida et al [35] reported that high serum potassium level was significantly and dosedependently associated with poor neurological outcomes. The highest proportion of favorable neurological outcome was 44.8% in Q1 group (K ≤3.8 mEq/L), and the proportion of favorable neurological outcomes decreased as the serum potassium level increased.…”
Section: Metabolic Managementmentioning
confidence: 99%
“…Potential variables included in the CRITICAL database that were measurable and available immediately after ROSC were included as candidate predictors, based on previous studies and expert opinion. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] We developed two prediction models using different sets of variables: model 1 included demographics, pre-hospitalisation and in-hospital information at the time of ROSC, except for laboratory data, and model 2 included all variables that contained the laboratory data available within 3 h of ROSC. The best level of consciousness to ICU admission was determined using the Glasgow Coma Scale motor score.…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…In general, anaerobic glycolysis due to inadequate oxygen delivery causes lactate and metabolic acidosis [27,28]. Furthermore, insu cient discharge of carbon dioxide due to low venous return and inappropriate ventilation provokes respiratory acidosis [29], which leads to the movement of potassium from the intracellular to the extracellular compartment [30]; thus, a longer duration of resuscitation is indicated by higher potassium levels in cardiac arrest patients [31]. Therefore, low pH value and higher lactate and potassium are indicative of hypoperfusion in vital organs, and longer duration of the resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low pH value and higher lactate and potassium are indicative of hypoperfusion in vital organs, and longer duration of the resuscitation. Moreover, elevated potassium levels are associated with cell lysis after cell death, and it may be indicative of the futility of resuscitation attempts [10,30,31] Thus, it is reasonable that pH values, lactate, and potassium levels can accurately predict their survival.…”
Section: Discussionmentioning
confidence: 99%